BRAND IMAGE AND ONLINE MARKETING ON PURCHASE INTEREST ON PASSION FRUIT SYRUP PRODUCTS IN MEDAN CITY - Tampubolon, Lasma Ria (ECOBISMA (JURNAL EKONOMI, BISNIS DAN MANAJEMEN), 2025)
Online marketing strategies can basically influence the steps taken by companies to improve product quality and consumer quantity effectively and efficiently. The existence of consumers has an influence on the company's ultimate achievement, namely making a profit through purchasing Passion Fruit Syrup products. This research aims to examine and analyze the influence of brand image and online marketing on purchase interest on Passion Fruit Syrup products in Medan City. The population in this study were consumers who purchased Passion Fruit Syrup products in Medan City. The number of samples used in the research was 150 respondents using the Cochran formula. The analysis technique used is the Partial Least Squares method, namely to test the measurement model and structural model. The research results show that brand image has no significant effect on purchase interest, online marketing has a significant effect on purchase interest